HIGHER SPIRITUAL QUOTIENT ENHANCES ADKAR COMPETENCIES - Areeba Javed; Dr. Leenah Askaree (Policy Research Journal, 2025)
The role of a higher Spiritual Quotient (SQ) in enhancing individual and organizational capabilities is becoming increasingly relevant in the context of modern change management frameworks such as ADKAR (Awareness, Desire, Knowledge, Ability, Reinforcement). This study investigates how a heightened SQ—characterized by self- awareness, ethical integrity, and a sense of meaning—can improve each component of the ADKAR model, thereby facilitating effective change management. Firstly, a higher SQ fosters deeper self-awareness, enabling individuals to better recognize and understand the need for change (Awareness). This self-awareness encourages a more reflective approach to personal and organizational transformation, reducing resistance and increasing door to new ideas. Secondly, the development of SQ enhances the Desire for change by aligning personal values with organizational goals. When individuals connect their work with a higher purpose, they are more motivated to engage in change initiatives, viewing them as opportunities for growth rather than challenges to overcome. Thirdly, SQ supports the acquisition of knowledge by promoting a learning mindset. A spiritually aware individual is often more open to continuous learning and personal development, which are critical in acquiring the skills and understanding necessary to implement change successfully. Fourthly, a higher SQ enhances the ability to apply new skills and behaviors in the workplace. This improvement in ability comes from a deeper sense of resilience and adaptability, traits that are nurtured through spiritual practices and ethical living. Finally, SQ plays a crucial role in Reinforcement by providing intrinsic motivation to sustain change. When individuals see the broader significance of their actions and how they contribute to a greater good, they are more likely to maintain new behaviors and support long-term change initiatives. In conclusion, integrating a higher Spiritual Quotient into the ADKAR framework can lead to more effective and enduring change management. By addressing the internal dimensions of change, SQ complements the technical aspects of ADKAR, creating a holistic approach that fosters both individual and organizational growth. This abstract highlights the transformative potential of SQ in cultivating a change-ready and resilient organizational culture.